Self-Regulation as a Control of Consumptive Behavior - Ratnamaya, Ni Putu Dinda Cetta; Dewi, Ni Luh Yulyana (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to examine the role of self-regulation as a key psychological mechanism in controlling impulsive and compulsive consumer behavior, particularly in the context of digital media influence. The objectives of the study were to determine how self-regulation influences consumer decision-making, analyze the interaction between intrapersonal communication and self-regulation, and propose strategies to reduce excessive consumer behavior among adolescents and young adults. The research method used a systematic literature review by analyzing scientific articles from various databases such as Google Scholar, ScienceDirect, ProQuest, and ResearchGate published in the last ten years. Data collection was carried out through keyword searches related to